Spatially Isotropic 3D Volumetric Reconstruction of Live Biological Cells with Multi-View Geometry - Lei, Yang; Shkolnikov, Viktor; Xin, Daisy (Proceedings (IEEE Conference on Multimedia Information Processing and Retrieval. Online), 2022)
3D cell models are important for understanding cellular structures, their relationships and dynamics. Currently these are obtained via highly specialized and expensive equipment, such as confocal microscopes, which require experts in microscopy and 3D reconstruction to produce time and labor-intensive insight into cellular dynamics. Furthermore, such reconstruction is generally spatially anisotropic. In contrast, we developed a system that performs volumetric reconstruction of live, biological cells in suspension that relies on standard fluorescence microscopy and performs automated, spatially isotropic 3D volumetric reconstruction. We rotate the cells using an electric field, while the video camera records 2D cell image sequences through the microscope. Our algorithm, the subject of this paper, then automatically reconstructs three-dimensional distributions of cellular structures. Here we define a linear mathematical model of the 3D reconstruction problem and solve it using the least square optimization method. We then demonstrate our system with the volumetric reconstruction of cellular structures in their endogenous state.